Changes in chemical properties of banana pseudostem, mushroom media waste, and chicken manure through the co-composting process - Islam, Mahammad Shariful; Kasim, Susilawati; Md. Alam, Khairul; Mohd Amin, Adibah; Tan, Geok Hun; Haque, Mohammad Amdadul (Multidisciplinary Digital Publishing Institute, 2021)
Co-composting is an effective approach to biowaste management. The co-composting potential of banana pseudostem (BPS) and mushroom media waste (MMW) with chicken manure (CM) has not been explored, let alone their suitable ratios of co-composting being determined. Meanwhile, the imbalance ratios of the feedstocks used in the process severely restrict the physicochemical properties and quality of the finished product. For this reason, six different ratios of BPS, MMW, and CM, viz. 1:1:1, 1:2:1, 1:3:1, 2:1:1, 2:2:1, and 2:3:1, respectively (T1–T6), were composted together in aerobic conditions to identify the suitable ratio by evaluating the changes in the physicochemical properties in the composting process. According to the ratio of treatments, the feedstocks were mixed on fresh weight basis. The turning process of co-composting piles was repeated at seven-day intervals to maintain the uniform aeration throughout the composting period. The piles having BPS, MMW, and CM at ratios of 1:2:1, 1:3:1, and 2:3:1, respectively, demonstrated a longer thermophilic phase, indicating more complete decomposition and earlier maturity compared to piles with higher amount of BPS. Of the ratios, BPS:MMW:CM at 1:2:1 ratio (T2) resulted in the highest total nitrogen (1.53%), lowest C:N ratio (12.4), organic matter loss (54.5%), and increased CEC (41.3 cmol/kg). The highest germination index (129%) was also recorded in the T2 compost, indicating that it was toxic-free and safe for seed germination. The nutrient-rich compost with high alkaline pH (≥10) can effectively ameliorate soils of an acidic nature, for example, the acidity of Ultisols and Oxisols.